Eficiência da Spirulina platensis como suplemento na alimentação do camarão marinho Litopenaeus vannamei - Silva, Manuel Messias Sinésio da (Universidade Federal Rural do Semi-Árido, 2021)
Aquaculture is responsible for cultivating aquatic organisms, shrimp farming with the production of marine shrimp of the Litopenaeus vannamei species, which is cultivated all over the world, stands out within this activity. However, as any activity has its difficulties, it faces the challenge of food management, which is where the highest production cost is concentrated. This is because the most important and expensive ingredient in feed formulation is protein. To meet the protein requirements in the rations, fishmeal is used, where the raw material for production comes from extractive fishing. As this ingredient has a high purchasing value, the need arose to look for possible alternative ingredients, such as by-products of some industries and unicellular organisms such as microalgae, in this case, especially Spirulina platensis, as it has numerous nutrients required by shrimp. The objective of this work was to evaluate the efficiency of Spirulina platensis as a supplement in the feeding of marine shrimp Litopenaeus vannamei. The experiment was carried out at the Aquaculture Sector at UFERSA, with a completely randomized design consisting of 4 treatments with 3 replications each. Shrimps were fed twice a day with commercial feed containing 30% crude protein and Spirulina platensis flour. The main physical-chemical parameters for the cultivation of the species were measured, such as dissolved oxygen, pH, temperature and salinity, where they remained within the recommended ideal range. Considering the results of zootechnical performance the average values of apparent feed conversion factor, average individual and final biomass showed significant difference between treatments, the average survival values remained high in all treatments with no significant difference between treatments. Thus, it is concluded that the addition of biomass of the microalgae Spirulina platensis in the feeding of marine shrimp of the species Litopenaeus vannamei behaves positively in the zootechnical development of these animals.
Keywords: Alimentação de camarão; Farinha de spirulina; Alimentos alternativos; Desempenho zootécnico; Proteína; ENGENHARIAS::ENGENHARIA DE PETROLEO